Psychiatry and Sports Medicine - Roeh A; Hasan A (Dynamic Media Sales Verlag, 2021)
Schizophrenia ranges among the most debilitating psychiatric diseases. Physical activity is recommended as an add-on therapy to improve acute symptoms (especially negative symptoms and cognitive deficits) and to prevent the onset of the disease. But individuals with schizophrenia usually engage in less physical activity than the general population.This sedentary lifestyle is one of the reasons that lead to more somatic comorbidities and increased mortality in this cohort. In this narrative review we provide an overview of evidence for the beneficial effects of physical exercise on the central nervous system and symptom severity in individuals with schizophrenia. We discuss the findings in the context of their implementation in current treatment guidelines: The guidelines only provide general advice and no concrete statements regarding type, duration and intensity of exercise therapies, as the existing studies varied in their methodology. Future studies should therefore explore the possibility to transfer existing detailed recommendations for the general population on patients with schizophrenia to reduce sedentary behavior.Key Words: Aerobic, Add-on therapy, Resistance Training, Prevention